2016
DOI: 10.7314/apjcp.2016.17.3.1123
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of Advanced and Recurrent Cervical Cancer Patients Treated with Chemotherapy: Experience of Northern Tertiary Care Hospital in Thailand

Abstract: Chemotherapy is the primary treatment for advanced and recurrent cervical cancer. To evaluate the survival outcomes of chemotherapy and the prognostic factors in this setting, we conducted a retrospective study by reviewing the medical records of advanced and recurrent cervical cancer patients treated with systemic chemotherapy at our institute between January, 2008 and December, 2014. One hundred and seventy-three patients met the criteria with a mean age of 50.9 years. 4.1% of them were HIV positive. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…At 3 years, the local control rate was 89.5e94.4%. At 3 years, DFS was 63.4e81.8% and overall survival was 64.6e89.5% [53,54]. Most of the published literature mentioned are from Thailand and China.…”
Section: South-east Asia and Chinamentioning
confidence: 99%
“…At 3 years, the local control rate was 89.5e94.4%. At 3 years, DFS was 63.4e81.8% and overall survival was 64.6e89.5% [53,54]. Most of the published literature mentioned are from Thailand and China.…”
Section: South-east Asia and Chinamentioning
confidence: 99%
“…A retrospective study in Thailand on 173 HIV-positive and HIV-negative patients (with a mean age of 50.9 years) with stage IVB cervical cancer showed modest efficacy, with overall median survival among all patients of 13.2 months. The only independent prognostic survival outcome was a recurrence-free interval of fewer than 12 months [24]. In Brazil, HIV was found not to be associated with mortality due to cervical cancer during the first year post-treatment, but the association was significant after more than 1 to 2 years post-diagnosis (overall mortality: adj HR = 2.02; 95% CI 1.27-3.22; cancerspecific mortality 4.35, 1.86-10.2) [25].…”
Section: Chemotherapymentioning
confidence: 99%
“…For the before-after studies, 6 out of 9 studies had a control group [20,23,25,27,29,32], specified inclusion and exclusion criteria, and defined exposure and outcome measures, and this also increased confidence that the reported improvements between before and after evaluations were not merely by chance. However, different participants' selection, small sample sizes, and short follow-up periods among other studies [20-22, 28, 31], including two descriptive studies [24,26] that did not mention how study participants were chosen or how exposure and outcomes measures were defined, might require their results to be interpreted with caution. Also, inadequate follow-up periods, failure to measure or include confounders in analyses, and lack of validity of reported outcomes might have resulted in some studies overestimated the effectiveness of the reported interventions.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%